The effect of creep and other time related factors on plastics. (PDL handbook series., 1991)
This handbook presents curve types for generic families of plastics. It provides test conditions, including temperature and applied stress, and contains creep property data for the following stress types: tension, flexure, impact, torsion, and compression. Data are compiled from various published and limited distribution sources, including commercial catalogs, journal articles, technical reports, materials information sheets, etc. Most of the test data is produced by the material manufacturers.